PENGARUH BIMBINGAN KELOMPOK TEKNIK SELF-MANAGEMENT UNTUK MEREDUKSI TINGKAT NOMOPHOBIA PADA SISWA KELAS VIII SMP N 37 SEMARANG - Asri Hapsari, Karisma (Cahaya Ilmu Bangsa Institute, 2024)
The development of technology in the era of globalization has made mobile phones an integral part of everyday life. However, dependence on cellphones, especially among adolescents, has led to the phenomenon of nomophobia or excessive fear when not holding a cellphone. This study aims to examine the effectiveness of group guidance with self-management techniques in reducing the level of nomophobia in class VIII students at SMP Negeri 37 Semarang. This type of research is quantitative with experimental method. This research used pretest-posttest control group design. The study population was students of class VIII A,B,D,E,F,G and H SMP N 37 Semarang in the 2024/2025 academic year. Sample taken is class VIII D and VIII E by using Simple Random Sampling technique. Data collection techniques in this study were obtained through observation, interviews and questionnaires. Based on the results of the posttest of the experimental class and the control class above, the experimental class obtained the highest score of 112 and the lowest score of 98 while in the control class the highest score was 82 and the lowest score was 50. Based on the results of the calculation of the difference test between the two means of the data presented in the table above, it is known in the Levene's test for equality of variance column that the significant value is 0.213 (p>0.05). Based on the results of the analysis, it can be concluded that there is an effect of group guidance with Self Management Techniques to Reduce the Level of Nomophobia in Class VIII Students of SMP Negeri 37 Semarang. Based on the results of the research that has been carried out, the researcher proposes several suggestions, namely: Group guidance services with self management techniques are very useful, so it is hoped that the school can implement the implementation of services with self management techniques